Assessment of the cellular localisation of the Annexin A2/S100A10 complex in human placenta - Abd El-Aleem, Seham; Dekker, Lodewijk V. (Springer, 2018)
The AnxA2/S100A10 complex has been implicated in various placental functions but although the localisation of these proteins individually has been studied, there is no information about the localisation of their complex in situ at the cellular level. Using the proximity ligation technique, we have investigated the in situ localisation of AnxA2/S100A10 complex in the placenta and have compared this with the location patterns of the individual proteins. High levels of expression of AnxA2/S100A10 complexes were observed in the amniotic membrane and in blood vessel endothelial cells. Lower levels were detected in the brush border area of the syncytium and in the trophoblasts. Immunohistochemical analysis of AnxA2 and S100A10 individually revealed broadly similar patterns of localisation. The brush border staining pattern suggests that in this location at least some of the AnxA2 is not in complex with S100A10. The formal location of the AnxA2/S100A10 complex is compatible with a role in cell-cell interaction, intracellular transport and secretory processes and regulation of cell surface proteases, implying contributions to membrane integrity, nutrient exchange, placentation and vascular remodelling in different parts of the placenta. Future applications will allow specific assessment of the association of the complex with pathophysiological disorders.